2018
DOI: 10.3390/ijgi7010023
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Clustering of Foreclosures in the Poorest-Quality Housing Urban Areas: Evidence from Catalan Cities

Abstract: This paper uses data on housing stock owned by financial entities as a result of foreclosures to analyze (1) the spatial logic of Spain's mortgage crisis in urban areas, and (2) the characteristics of the types of housing most affected by this phenomenon. Nearest-Neighbor Index and Ripley's K function analyses were applied in two Catalan cities (Tarragona and Terrassa). The results obtained show that foreclosures tend to be concentrated in the most deprived neighborhoods. The general pattern of clustering also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
1
12
0
2
Order By: Relevance
“…The urban dimension has also been dealt with using non-official sources such as the portals for sale of used housing belonging to financial institutions. To be exact, using the geo-location of housing for sale by banks, Gutiérrez and Arauzo-Carod (2018) and Delclòs (2016, 2017), for the cases of Tarrasa and Tarragona, as well as Gutiérrez and Domènech (2017a), for Lleida, concluded that evictions have tended to be concentrated in the most disadvantaged districts and the lower-quality housing, a fact which has reinforced the urban inequalities in these cities. Gutiérrez and Domènech (2017b) for Alicante, Murcia and Zaragoza have reached the same conclusions, using as territorial information the housing sold by the SAREB (Asset Management Company from Bank Restructuring).…”
Section: Studies On the Social Dimension Of Real Estate Dispossessionmentioning
confidence: 99%
“…The urban dimension has also been dealt with using non-official sources such as the portals for sale of used housing belonging to financial institutions. To be exact, using the geo-location of housing for sale by banks, Gutiérrez and Arauzo-Carod (2018) and Delclòs (2016, 2017), for the cases of Tarrasa and Tarragona, as well as Gutiérrez and Domènech (2017a), for Lleida, concluded that evictions have tended to be concentrated in the most disadvantaged districts and the lower-quality housing, a fact which has reinforced the urban inequalities in these cities. Gutiérrez and Domènech (2017b) for Alicante, Murcia and Zaragoza have reached the same conclusions, using as territorial information the housing sold by the SAREB (Asset Management Company from Bank Restructuring).…”
Section: Studies On the Social Dimension Of Real Estate Dispossessionmentioning
confidence: 99%
“…Both ANN and Ripley's K-function are best suited to analyzing the type of spatial distributions. They help avoid the modifiable areal unit problem [69] as they treat space as continuous, without constraining data within any regions or units, and, contrary to the quadrat method, they are free from statistical bias caused by data aggregation [70]. Nevertheless, Ripley's K and NN functions describe different aspects of a point process.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that around 30% of these properties derive from dispossession processes (not necessarily judicial ones). This fact has given rise to a series of geographical studies on the cities of Lleida [28], Tarragona, Terrassa and Salt [29][30][31], Alicante, Murcia and Zaragoza [32]; Madrid [33] as well as the total of housing properties owned by SAREB in all Spanish municipalities [34]. With a similar approach, some insights offered from other fields are also worth mentioning, as is the case of Raya [35], whose research focuses on the autonomous communities of Madrid and Valencia.…”
Section: Current Status Of the Issuementioning
confidence: 99%